Influence of different processing and storage conditions on in vitro bioaccessibility of polyphenols in black carrot jams and marmalades. (1st November 2015) - Kamiloglu, Senem; Pasli, Ayca Ayfer; Ozcelik, Beraat; Van Camp, John; Capanoglu, Esra
Highlights: Black carrot jams and marmalades are good sources of polyphenols. Processing decreased total phenolics, antioxidant capacity and phenolic acids. Storage at 4 °C resulted in higher retention of phenolics than storage at 25 °C. Processing led to increases in percent recovery of bioaccessible phenolics. Abstract: Black carrot is indicated to play an important role in nutrition, as it comprises a variety of health-promoting components, including polyphenols. The objective of the present study was to monitor the stability of total phenolics, antioxidant capacity and phenolic acids in black carrot jams and marmalades after processing, storage and in vitro gastrointestinal digestion. Total phenolic content and antioxidant capacity were determined using spectrophotometric methods, whereas phenolic acids were identified using HPLC–PDA. Jam and marmalade processing significantly decreased total phenolics (89.2–90.5%), antioxidant capacity (83.3–91.3%) and phenolic acids (49.5–96.7%) ( p  < 0.05). After 20 weeks of storage, the percent decrease in total phenolics in samples stored at 25 °C (26.4–48.0%) was slightly higher than the samples stored at 4 °C (21.0–42.5%). In addition, jam and marmalade processing led to increases in the percent recovery of bioaccessible total phenolics (7.2–12.6%) and phenolic acids (4.7–31.5%), as well as antioxidant capacity (1.4–8.1%). In conclusion, current study highlighted black carrot jams and marmalades as good sources of polyphenols, with high bioaccessibility levels.